Oral cavity cancer treatment outcomes in Western Australia - Hendriks, Thomas; Cardemil, Felipe; Sader, Chady (Australian Journal of Otolaryngology; Vol 2 (July 2019): Australian Journal of Otolaryngology, 2019)
Background: Oral cavity cancers (OCC) account for a significant proportion of head and neck malignancies and pose a significant disease burden given the poor quality of life outcomes and high mortality rates. We evaluated the treatment outcomes of OCC treated at Sir Charles Gairdner Hospital (SCGH), Western Australia (WA). Methods: A retrospective cohort study was conducted at one of the largest tertiary hospitals in the state. The hospital-based cancer registry was used as a primary source of data, including cases presented between January 2012 and December 2016. Review of medical records was performed for those patients with missing data. The study was approved by the Institutional Safety Board (ISB) in accordance with the hospital regulations (SCGH). Results: One hundred and one patients with primary diagnosed OCC received treatment during the period. The majority of patients were male, and most were treated primarily with surgery. Twenty-six patients (25.7%) developed recurrence during follow-up, with a median time to recurrence of 10.5 months. Of the patient with recurrence, 73% (19/26) died because of their recurrence. A total of 38 patients died during follow-up (37.6%), with a 3-year overall survival of 66.3% (95% CI, 55.2–75.2%), and a 3-year disease-specific survival (DSS) of 83.2% (95% CI, 72.2–90.1%). Conclusions: OCC continues to be a therapeutic challenge for the head and neck surgeon. Given the relatively asymptomatic nature of early disease, OCC diagnosed at a late stage is not uncommon, therefore positive lymph-nodes are important when evaluating survival. This study examines up-to-date treatment outcomes for OCC in WA and highlights the variation in mortality rates observed globally.